2016
DOI: 10.1002/da.22467
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Oxytocin Concentration and Depressive Symptoms: A Review of Current Evidence and Directions for Future Research

Abstract: There is substantial recent interest in the role of oxytocin in social and affiliative behaviors— animal models of depression have suggested a link between oxytocin and mood. We reviewed literature to date for evidence of a potential relationship between peripheral oxytocin concentration and depressive symptoms in humans. Pubmed® and PsychINFO® were searched for biomedical and social sciences literature from 1960 – May 19, 2015 for empirical articles in English involving human subjects focused on the relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 39 publications
1
30
0
1
Order By: Relevance
“…Similar findings have been reported previously in small samples of depressed females (Ozsoy et al, 2009;Yuen et al, 2014). Overall, however, very few previous studies have examined oxytocin levels in MDD versus healthy controls, and findings are inconsistent (Massey et al, 2016). This may be due to small sample sizes, heterogeneity in study designs, and other methodological limitations (Massey et al, 2016).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Similar findings have been reported previously in small samples of depressed females (Ozsoy et al, 2009;Yuen et al, 2014). Overall, however, very few previous studies have examined oxytocin levels in MDD versus healthy controls, and findings are inconsistent (Massey et al, 2016). This may be due to small sample sizes, heterogeneity in study designs, and other methodological limitations (Massey et al, 2016).…”
Section: Discussionsupporting
confidence: 71%
“…Overall, however, very few previous studies have examined oxytocin levels in MDD versus healthy controls, and findings are inconsistent (Massey et al, 2016). This may be due to small sample sizes, heterogeneity in study designs, and other methodological limitations (Massey et al, 2016). The current results suggest a need for further research into relationships between depressive symptoms and oxytocin.…”
Section: Discussionmentioning
confidence: 74%
“…Another study found lower oxytocin levels during breastfeeding at 8 weeks postpartum in women with depressive symptoms compared to asymptomatic women (Cox, et al, 2015). However, one study found that higher oxytocin in the third trimester predicted higher depressive symptom severity at 6 weeks postpartum, but only in women with a prior history of depression; plasma oxytocin was unrelated to symptom severity in women without a history of depression (Suena H. Massey, et al, 2016). And finally, a very recent longitudinal study of women whose plasma oxytocin was measured twice during pregnancy and at 3 different times postpartum, found that rather than absolute plasma oxytocin levels, the timing of fluctuations in oxytocin levels from pregnancy to 6 months postpartum differed significantly in women with postpartum depressive symptoms compared to those without (Jobst et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Failed lactation (Stuebe, Grewen, Pedersen, Propper, & Meltzer-Brody, 2011) and symptoms of depression are associated with differences in oxytocin activity (Stuebe et al, 2013), and it has been postulated that endogenous oxytocin may protect against the adverse depressive effects of psychosocial stress on mothers (Zelkowitz et al, 2014). A recent review underscores the importance of reproductive and perinatal stage in associations between oxytocin and depression (Massey, Backes, & Schuette, 2016). Despite these clinical observations and interest in oxytocin as a treatment for perinatal depression and anxiety, there has been little investigation of the potential effects of clinical peripartum manipulation through the use of synthetic oxytocin.…”
Section: Introductionmentioning
confidence: 99%
“…37,38 A recent systematic review of eight studies revealed an inverse relationship between peripheral OT and depressive symptom severity in pregnant women, but associations between depressive symptom severity and high, low, and variable OT levels in non-pregnant women. 39 In men, peripheral OT and depressive symptoms were positively but not significantly associated. A meta-analysis of 64 studies of several psychiatric disorders, including MDD but not PTSD, showed no significant differences in peripheral OT between healthy and psychiatric groups (except in anorexia).…”
Section: Oxytocinmentioning
confidence: 94%